Disinfection of zygotic embryos of Ceroxylon alpinum Bonpl. for in vitro establishment - Serna-Toro, Estefany (2025)
Introduction. The genus Ceroxylon comprises vulnerable Andean palm species threatened by humanintervention. Ceroxylon alpinum Bonpl. seeds specifically exhibit low germination rates, slow growth, and requirecomplex environmental interactions for development. Objective. To evaluate disinfection methods for zygotic palm embryos to facilitate in vitro cultivation and micropropagation. Materials and methods. Research was conductedbetween February 2021 and March 2022. Wax palm (Ceroxylon alpinum Bonpl.) seeds were harvested during the fruiting stage in El Cairo forest, Salento, Quindío, Colombia, selecting specimens with optimal morphological development and phytosanitary conditions. Seeds were transferred to the Plant Biotechnology Laboratory-CIBUQ in Armenia, Quindío. Surface sterilization was performed using neutral detergent Tween 20 at a concentration of 0.1 % (v/v) and running water, followed by immersion in 3 % NaClO for 25 minutes. Embryos were extracted under a stereoscope and immersed in 70 % alcohol for one minute. Subsequently, they underwent different NaClO concentration treatments for 10 minutes before being cultivated in Murashige & Skoog (MS) medium and evaluated for eight weeks. A completely randomized design with a single factor (NaClO concentration) and three levels (1 %, 1.5 %, and 2 %) was used, analyzed through analysis of variance and Tukey’s test (α = 0.05) using Statistica 8 software. Results. Disinfection with 1.5 % NaClO (T2) demonstrated optimal efficacy, yielding 75 % survival and 74 % embryo sprouting rates. In contrast, 2 % NaClO concentration resulted in increased contamination. Conclusion. The disinfection method using 1.5 % NaClO proved most effective for enabling the viability of wax palm zygotic embryos, maximizing in vitro survival and sprouting, thereby enhancing prospects for micropropagation and conservation of this endangered species.